Model of Academic Service Quality at School of Management and Informatics in Bandung, Indonesia. - Marjito, Marjito; Komarudin, Komarudin (Archives of Business Research, 2017)
The globalization era and the rapid technological developments lead to the high demand of qualified human resources. Thus, educational institutions must produce qualified and highly competitive graduates. . Otherwise, there will be a gap between the human resources with the market needs. The excellent academic service quality for the students is important to reach the goal. The expected services are curriculum service, Teaching and Learning Process, the supporting facilities and infrastructure for Teaching and Learning Process and the supporting system of academic service support. However, the laboratories equipments have not supported the market needs. This study aims to to describe the policy of academic service quality, implementation, monitoring and model of academic service quality improvement in a School of Management and Informatics in Bandung. Moreover, this research uses qualitative naturalistic approach with descriptive method and case study. This study collects the data through interview, observation and document study. Data analysis is done through data display process, data reduction, and data verification through triangulation process. The results show that the curriculum policy has not used the concept of link and match. Theoretically, problems does not exist in the Teaching and Learning process. However, in reality the Teaching and Learning process has not met the users need yet. Furthermore, the there are no monitoring activities both in learning-teaching activities and the practice.